Penentuan Waktu Salat: Antara Tradisionalisme dan Modernisme - Rusdin Muhalling (Al-'Adl, 2017)
Penelitian this is a study, with the study of Science Falak as arithmetic, to be used by Muslims in the practice of daily worship, particularly worship prayer, fasting and pilgrimage. The subject is the preliminary determination of the time of prayer, precisely and thoroughly based on the regional data and the formula of prayer time. The discussion in penelitian this, is the determination of the times of prayer between traditionalism and moderenisme, performed traditional and modern with the theory and practice, how astronomy as arithmetic, determine the start time of prayer precisely and accurately in a place, accuracy and thoroughness can be demonstrated and justified Scientifically, based on the initial formula of prayer time. The initial determination of the times of prayer, the beginning of Ramadan, one of Syawal and Zulhijjah, And the determination of Eid-ul-Fitr and Eid al-Adha, as well as great days for Muslims. The results of hisab and Rukyah can be proven and accounted for scientifically. The results showed that the science of Falak as the science of reckoning is very useful for Muslims in setting the times of worship. Such as setting the beginning of the month of Ramadan, the direction of Qiblah, set the time to break the fast and the time of dawn. Set a start and finish time of fasting Ramadan, set Idul Fitri and Idul Adha, Position The direction in an area, starting with the methods or practical ways, namely matode (Reckoning) and methods Rukyat.